Cementing Strategies in Yehudit Kafri's Zosha: From the Jezreel Valley to the Red Orchestra - Raizen, Esther (Hebrew studies, 2018)
The paper examines Yehudit Kafri's biographical novel Zosha: From the Jezreel Valley to the Red Orchestra (2003) through the lens of two cementing themes she uses as a strategy for piecing together the lives of her main characters. Leaning on a perspective that categorically separates the good from the evil players of the War World II era, Kafri applies an atomized approach to the reconstruction of her characters' life stories, allowing their collective backgrounds to surface inseparably from their individuality. As her main cementing strategy, Kafri translates her understanding of the integrative role of the mother in Polish-Jewish families during the interwar years into an argument on motherly love (or its absence) as a key to the development of one's insistence on the right to life, and, by extension, on the right of Jews to live as a people in the land of Israel. In parallel, Kafri builds up the theme of Jewishness as an activist, secular worldview held by Hashomer Hatza'ir and communist youth, dictating the choices they had made in their early years and into their adulthood. Pointing out Kafri's systematic reliance on these two themes, I present her as an agent of memory for her parents' generation, one who deliberately avoids irony and derision while addressing with full honesty the difficult questions encountered by that generation and bequeathed to the generations to follow, among them the question about the exclusion of Zosha and others like her from the Israeli collective agent of memory.